Louis XIV and the Parlements: The assertion of royal authority - Hurt, John (Manchester University Press, 2002)
This is the first scholarly study of the political and economic relationship between Louis XIV and the parlements of France, the Parlement of Paris and all the provincial tribunals. The author explains how the king managed to overcome the century-old opposition of the parlements to new legislation, and to impose upon them the strict political discipline for which this reign, and only this reign, is known. Hurt shows that the king built upon that discipline to extract large sums of money from the judges in the parlements, notably in the form of forced loans and office sales, thus damaging their economic interests. When the king died in 1715, the regent, Philippe d'Orléans, after a brief attempt to befriend the parlements through compromise, resorted to the authoritarian methods of Louis XIV and perpetuated the Sun King's political and economic legacy. This study calls into question the current revisionist understanding of the reign of Louis XIV and insists that, after all, absolute government had a harsh reality at its core. Based upon extensive archival research, Louis XIV and the parlements will be of interest to all students of the history of early modern France and the monarchies of Europe.